Astroglial water channel aquaporin 4-mediated glymphatic clearance function: A determined factor for time-sensitive treatment of aerobic exercise in patients with Alzheimer's disease. (October 2018) - Yin, Mengmei; Pu, Tinglin; Wang, Linmei; Marshall, Charles; Wu, Ting; Xiao, Ming
Abstract: Currently, there are no effective drug therapies for Alzheimer's disease (AD). Thus, exploring new non-pharmacological strategies, including the neuroprotective mechanisms of aerobic exercise, to enhance therapeutic treatment of AD are essential. Previous studies have shown that the beneficial efficiency of aerobic exercise in the prevention and treatment of AD is time-sensitive, but its mechanism is not clear. Recent studies revealed that the water channel protein aquaporin 4 (AQP4) mediates the glymphatic system to clear interstitial solutes, including β-amyloid, from the brain. More recently, voluntary exercise has been shown to promote glymphatic clearance function in mice. However, glymphatic function is reduced in the mid- or late-stage of AD due to the loss of the polarity distribution of AQP4. Based on this, we hypothesized that AQP4-mediated glymphatic system clearance function is a determining factor for time-sensitive treatment of aerobic exercise in patients with AD. While further studies are necessary, the potential results are important for elucidating the new pro-cognitive mechanism of aerobic exercise, but also help to establish a new strategy for treatment of AD via regulation of glymphatic clearance function by targeting AQP4.